A Randomized, Double-Blind, Multicenter Clinical Study Comparing the Efficacy and Safety of a Drug Combination of Lopinavir/Ritonavir-Azithromycin, Lopinavir/Ritonavir-Doxycycline, and Azithromycin-Hydroxychloroquine for Patients Diagnosed with Mild to Moderate COVID-19 Infections. (9th February 2021) - Purwati,; Budiono,; Rachman, Brian Eka; Yulistiani,; Miatmoko, Andang; Nasronudin,; Lardo, Soroy; Purnama, Yongki Iswandi; Laely, Mafidhatul; Rochmad, Ike; Ismail, Taufik; Wulandari, Sri; et al.
Abstract : Background . At the present time, COVID-19 vaccines are at the testing stage, and an effective treatment for COVID-19 incorporating appropriate safety measures remains the most significant obstacle to be overcome. A strategic countermeasure is, therefore, urgently required. Aim . This study aims to evaluate the efficacy and safety of a combination of lopinavir/ritonavir-azithromycin, lopinavir/ritonavir-doxycycline, and azithromycin-hydroxychloroquine used to treat patients with mild to moderate COVID-19 infections. Setting and Design . This study was conducted at four different clinical study sites in Indonesia. The subjects gave informed consent for their participation and were confirmed as being COVID-19-positive by means of an RT-PCR test. The present study constituted a randomized, double-blind, and multicenter clinical study of patients diagnosed with mild to moderate COVID-19 infection. Materials and Methods . Six treatment groups participated in this study: a Control group administered with a 500 mg dose of azithromycin; Group A which received a 200/50 mg dose of lopinavir/ritonavir and 500 mg of azithromycin; Group B treated with a 200/50 mg dose of lopinavir/ritonavir and 200 mg of doxycycline; Group C administered with 200 mg of hydroxychloroquine and 500 mg of azithromycin; Group D which received a 400/100 mg dose of lopinavir/ritonavir and 500 mg of azithromycin; and Group E treated with a 400/100 mg dose of lopinavir/ritonavir and 200 mg of doxycycline. Results . 754 subjects participated in this study: 694 patients (92.4%) who presented mild symptoms and 57 patients (7.6%) classified as suffering from a moderate case of COVID-19. On the third day after treatment, 91.7%–99.2% of the subjects in Groups A–E were confirmed negative by a PCR swab test compared to 26.9% in the Control group. Observation of all groups which experienced a significant decrease in virus load between day 1 and day 7 was undertaken. Other markers, such as CRP and IL-6, were significantly lower in all treatment groups (p < 0.05 and p < 0.0001 ) than in the Control group. Furthermore, IL-10 and TNF- α levels were significantly elevated in all treatment groups (p < 0.0001 ). The administration of azithromycin to the Control group increased CRP and IL-6 levels, while reduced IL-10 and TNF- α on day 7 (p < 0.0001 ) compared with day 1. Decreases in ALT and AST levels were observed in all groups (p < 0.0001 ). There was an increase in creatinine in the serum level of the Control, C, D, and E groups (p < 0.05 ), whereas the BUN level was elevated in all groups (p < 0.0001 ). Conclusions . The study findings suggest that the administration of lopinavir/ritonavir-doxycycline, lopinavir/ritonavir-azithromycin, and azithromycin-hydroxychloroquine as a dual drug combination produced a significantly rapid PCR conversion rate to negative in three-day treatment of mild to moderate COVID-19 cases. Further studies should involve observation of older patients with severe clinical symptoms in order to collate significant amounts of demographic data.